The big bounce - Leonard, Elmore, 1925-2013 (Robert Hale, 2001)
"But the whole deal, staying and going along with her idea, both, depended really on how much nerve he had. Which she would have to find out..." Nancy Hayes has plenty of feminine charm - and the instincts of a shark. Jack Ryan is handy with his fists, and has all the cunning of an ex-con. Now, in a Michigan resort town, a rich man wants Jack gone and Nancy for himself. For Jack, the choice is clear: Nancy's promises of pleasure, her crazy, thrill-seeking schemes of breaking into homes, shooting guns and maybe stealing a whole lot of money is driving him mad. But there is one thing Jack doesn't know yet. Nancy is planning the deadliest thrill of all.